PEMBERDAYAAN PENGHUNI RUMAH SINGGAH DISOSPERMADES BANYUMAS MELALUI KEGIATAN BAKTI SOSIAL - Anggara Setya Saputra; Devit Bagus Indranika; Nidya Ayu Wulandari Ramdan; Sartono Sartono (Department of Public Administration, University Wijaykusuma Purwokerto, 2026)
This community service activity aims to provide assistance and empowerment to residents of Rumah Singgah Disospermades Banyumas through social service programs. The subjects of this activity were residents of Rumah Singgah consisting of homeless people, neglected people (PGOT), and people with mental disorders (ODGJ). The method used was a participatory approach involving residents, shelter managers, and companions in every stage of activity. Data collection was carried out through direct observation and evaluative discussions with shelter managers. The activities carried out included providing basic needs assistance, exercise together, painting as creative therapy, as well as various recreational and educational activities. The results showed that social service activities were able to increase the participation and social interaction of residents, strengthen psychosocial conditions through creative activities, and improve the physical health of residents. However, there were obstacles related to differences in the psychological conditions of residents which required a more sustainable and flexible approach. This activity demonstrates that participatory-based empowerment programs can have a positive impact on the quality of life of Rumah Singgah residents and can be a strategic model for social rehabilitation of vulnerable groups in society.